2017
DOI: 10.1177/0363546517690525
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postoperative KT-1000 Arthrometer Score on Long-Term Outcome After Anterior Cruciate Ligament Reconstruction

Abstract: Postoperative laxity of greater than 5 mm STS difference as measured by KT-1000 arthrometer does not appear to place patients at a worse clinical outcome at long-term follow-up, nor does it lead to significantly more subsequent procedures. In addition, transtibial ACLR can provide excellent clinical results at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
0
24
1
1
Order By: Relevance
“…While the bulk of the current literature supports better results with single-bundle grafts positioned in the middle of both insertions, it is not yet clear that the anisometry associated with this graft position—despite being similar to the native ACL—is desirable. While a recent long-term follow-up study suggests even abnormally increased graft lengthening may be very well tolerated clinically, 15 recent reports imply that even better graft function might be achieved by choosing femoral tunnel positions prioritized less on the geometric center of the femoral insertion and more on a “functional” center where the most important elements of the ligament exist. 26 , 37 For the purposes of our study results, it is important to note that our investigation was never intended to endorse one graft position over another—only to evaluate HTT, AM portal, and TT abilities to position grafts in the best way the literature currently suggests.…”
Section: Discussionmentioning
confidence: 99%
“…While the bulk of the current literature supports better results with single-bundle grafts positioned in the middle of both insertions, it is not yet clear that the anisometry associated with this graft position—despite being similar to the native ACL—is desirable. While a recent long-term follow-up study suggests even abnormally increased graft lengthening may be very well tolerated clinically, 15 recent reports imply that even better graft function might be achieved by choosing femoral tunnel positions prioritized less on the geometric center of the femoral insertion and more on a “functional” center where the most important elements of the ligament exist. 26 , 37 For the purposes of our study results, it is important to note that our investigation was never intended to endorse one graft position over another—only to evaluate HTT, AM portal, and TT abilities to position grafts in the best way the literature currently suggests.…”
Section: Discussionmentioning
confidence: 99%
“…KT-1000 is an objective measure of AP knee laxity that, although a good research tool and easily standardised among patients, has been heavily criticised for lack of associating its measures to clinical outcomes 19. One such explanation is that it solely measures the passive restraints of the ligament in one plane, while the dynamic stabilisers (ie, muscles) remain silent 20. Tests of rotational laxity, such as the Pivot Shift test, involve more planes of movement and correlate better to PROMs 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Each patient underwent clinical examinations at 2 years after surgery. The side-to-side difference in anterior laxity was measured with a KT-2000 arthrometer (Medmetric) at 30° of knee flexion under an anterior drawer force of 133 N, although Goodwillie et al 16 found that the side-to-side difference may play less of a role in clinical outcomes. A well-trained physical therapist and a surgeon, who were blinded to the surgical timing, collected the KT-2000 arthrometer results postoperatively.…”
Section: Methodsmentioning
confidence: 99%